YOUNG ISOLATED SYSTOLIC HYPERTENSION DIFFER ACCORDING TO THE LEVEL OF PHYSICAL ACTIVITY. (June 2018) - Saladini, F.; Fania, C.; Mos, L.; Mazzer, A.; Casiglia, E.; Palatini, P.
Abstract : Objective: Little is known about the clinical significance and the management of isolated systolic hypertension in the young (ISHY). According to some authors ISHY is often associated with athletic participation and is considered at low cardiovascular risk whereas according to others ISHY subjects are characterized by increased BMI associated with metabolic abnormalities. The aim of the present study was to investigate whether in athletes ISHY has different clinical characteristics and better long-term evolution than ISHY in sedentary subjects. Design and method: We examined 35 male athletes with ISHY (ISHY-Athl), with a mean age of 23.6 ± 7.0 years and blood pressure of 152.7 ± 12.0 mmHg and 35 age-matched sedentary ISHY subjects (ISHY-Sed). Thirty-five age-matched normotensives (NTs), and 35 subjects with systolic-diastolic hypertension- (SDH) were also enrolled. All these conditions were identified with ambulatory blood pressure (BP) monitoring. All data were re-measured after 8 years of follow-up. Results: ISHY-Athl had lower 24 h hear rate than the other 3 groups (p for ANOVA = 0.001). In addition, they had higher stroke volume (89.2 ± 16.2 ml, p< = 0.01 versus other 3 groups). Peripheral resistance was similar in ISHY-Athl and NT, whereas it was increased in the ISHY-Sed and SDH participants (p < 0.05). BMI and metabolic data at baseline did not differ between the 4 groups. After 8 years, changes in 24 h BP were similar in the ISHY-Athl and ISHY-Sed. Likewise, changes in BMI and metabolic data did not differ between these two groups. Conclusions: Athletes with ISHY exhibited a different hemodynamic pattern characterized by elevated stroke volume and normal peripheral resistance compared to ISHY with sedentary habits. However, baseline BMI and metabolic profile and the evolution of BP and metabolic data in ISHY subjects did not differ according to physical activity habits.